Design of an Electric Network for the Norhtern part of the West Bank of Palestine taking into consideration a new generation bus - No'man, Ikhlas; Abbas, Raghda; Bani Odhe, Dana (My University, 2017)
Design of an Electric Network for the Northern part of the West Bank of Palestine taking into consideration a new generation bus This project has studied the design and analysis of an electrical network for Northern part of the West Bank, in particular, (Jenin, Tubas, & Tulkarem) cities, which will be suplied from Al-Jalama substation in Jenin city. And (Nablus, Selfet, & Qalqelia) cities , which will be supplied from Sarra substation in Nablus city. This project will seek for the best choices to design a power network and analysis to obtain the best performance, reduce power losses and achieve the best economical rewards, study the balance of real power and reactive power and the power factor correction ,and the load flow ,& ETAP program will be used to achieve this load flow. In this project we aim to design an integrated electrical network with standard voltages, low power losses, high quality electrical energy, high reliability, good voltage level, and low transmission cost. This project will be clarified by first designing Al-Jalama electrical network, second designing Sarra electrical network, then make connection between these two networks. In this project we will study many differnet design for both electrical network (ALJalama , & Sarra ) to choose the best design technically and economically. Power losses are quite high in the West Bank , a key source of technical losses results from the low power factors found in the West Bank. Non-technical losses result from thief, unpaid bills and any other illegal ways of accessing the network. The capacity of sub-stations will enough the West bank of Palestine for two years at most , then other sources should be found to cover the lake of electricity. The best source could be solar energy projects, since the peak of energy consumption in the Palestinian land occurs in summer times. In past, Some loads in the north are fed directly from 161 kV substations inside Israel like Tulkarem and Qalqelia. Same thing with Jenin and Tubas are supplied by 33 kV feeders from Beisan in Israel. But recently, Jenin and Tubas are supplied by 33 KV feeders from Al-Jalama, while tulkarem are supplied by 22KV from Al-Jalama. Our standards in this project was specified by cities loads, and future expanded load, so our studied covers the need for electricity for the next three years. The project has discussed an important issue in Palestine, since Palestine face a lack in electricity, & this project studies the optimum electrical network design for three cities in Palestine, which are Jenin, Tubas, Tulkarem. The special thing about this project, is that it studies the electrical network distribution for Jenin, Tubas, & Tulkarem which will be provided by electricity from a new substaion (Al-Jalama substation). Another network was studied which is Sarra network and it supplies Salfeet, Nablus, and Qalqelia cities, then we connected both of optimum network designs. the single-line diagram has been validated, the equipment is chosen and sized, then we choose the protection devices which allowing faults to be detected and cleared.